2022
DOI: 10.1523/jneurosci.0307-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Brain Wiring Diagram of Oxytocin System in Adult Mice

Abstract: Oxytocin (Oxt) neurons regulate diverse physiological responses via direct connections with different neural circuits. However, the lack of comprehensive input-output wiring diagrams of Oxt neurons and their quantitative relationship with Oxt receptor (Oxtr) expression presents challenges to understanding circuit-specific Oxt functions. Here, we establish a whole-brain distribution and anatomic connectivity map of Oxt neurons, and their relationship with Oxtr expression using high-resolution 3D mapping methods… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 57 publications
(92 reference statements)
2
48
2
Order By: Relevance
“…In our recent publication, we quantified and compared Oxt projections and OxtR density in the whole mouse brain. Except for regions within the thalamus and medulla, our analysis revealed no significant quantitative correlation between Oxt projection and OxtR density in most brain areas ( Son et al, 2022 ). For example, most regions within the cerebral cortex of the mouse brain are enriched with OxtRs, but the Oxt projection fibers are sparse.…”
Section: Mismatch Between Oxt Projections and Oxtr: Implications On O...contrasting
confidence: 58%
See 3 more Smart Citations
“…In our recent publication, we quantified and compared Oxt projections and OxtR density in the whole mouse brain. Except for regions within the thalamus and medulla, our analysis revealed no significant quantitative correlation between Oxt projection and OxtR density in most brain areas ( Son et al, 2022 ). For example, most regions within the cerebral cortex of the mouse brain are enriched with OxtRs, but the Oxt projection fibers are sparse.…”
Section: Mismatch Between Oxt Projections and Oxtr: Implications On O...contrasting
confidence: 58%
“…Oxt is synthesized mainly in the paraventricular hypothalamus (PVH) and the supra optic nucleus (SO) along with a smaller number of neurons in the accessory nuclei of the hypothalamus and extended amygdala ( Freda et al, 2022 ; Son et al, 2022 ). In addition, our recent study identified a dense cluster of Oxt neurons in the tuberal nucleus area (TU) of the hypothalamus in the mouse brain ( Son et al, 2022 ).…”
Section: Neuroanatomy and Functions Of Oxt Neuronsmentioning
confidence: 99%
See 2 more Smart Citations
“…Though previous studies suggested that oxytocin system could act differently in males and females [ 13 , 73 75 ], the neuronal properties and projections of PVN oxytocin neurons are found to be sex invariance in mice [ 76 , 77 ], and the modulation function of oxytocin signal in visual cortex was reported to be similar in different genders [ 15 , 16 ]. In our study, we compared the differences in retinal oxytocin signals between males and females in the following four aspects: (1) Oxtr fluorescence intensities in the INL and GCL are not significantly different between males and females (Additional file 1 : Fig.…”
Section: Discussionmentioning
confidence: 99%